Review article: autoimmune hepatitis – current management and challenges. Issue 8 (8th September 2013) - Zachou, K.; Muratori, P.; Koukoulis, G. K.; Granito, A.; Gatselis, N.; Fabbri, A.; Dalekos, G. N.; Muratori, L.
Summary Background Autoimmune hepatitis (AIH) is a disease of unknown aetiology characterised by interface hepatitis, hypergammaglobulinaemia, circulating autoantibodies and a favourable response to immunosuppression. Aim To review recent advancements in understanding aetiopathogenesis, clinical, serological and histological features, diagnostic criteria and treatment strategies of AIH. Methods Published studies on AIH extracted mainly from PubMed during the last 15 years. Results Autoimmune hepatitis has a global distribution affecting any age, both sexes and all ethnic groups. Clinical manifestations are variable ranging from no symptoms to severe acute hepatitis and only seldom to fulminant hepatic failure. Autoimmune attack is perpetuated, possibly via molecular mimicry mechanisms, and favoured by the impaired control of regulatory T‐cells. A typical laboratory finding is hypergammaglobulinaemia with selective elevation of IgG, although in 15–25% of patients – particularly children, elderly and acute cases – IgG levels are normal. Liver histology and autoantibodies, although not pathognomonic, still remain the hallmark for diagnosis. Immunosuppressive treatment is mandatory and life‐saving; however, to meet strict response criteria, the conventional therapy with prednisolone with or without azathioprine is far from ideal. Conclusions Autoimmune hepatitis remains a major diagnostic and therapeutic challenge. The clinician, the hepato‐pathologist and the laboratory personnel need to become more familiar with different expressions of the disease, interpretation of liver histology and autoimmune serology. According to the strict definition of treatment response issued by the 2010 AASLD guidelines, many patients are nonresponders to conventional treatment. Newer immunosuppressive agents targeting pathogenetic mechanisms can improve patient management, which needs to be tailored on a case‐by‐case basis.